Aves insetívoras e sua relação com taxas de folivoria no Parque Estadual Carlos Botelho, SP - Gagetti, Bruna Leone (2015)
Birds contribute to many kinds of environmental services, such as predation on arthropods, which results in their population control, and reduced folivory and higher growth rates of plants. In addition, insectivorous birds are sensitive to environmental disturbances, requiring protected areas for conservation and being indicators of environmental quality. In this research, we sampled the insectivorous birds and tested whether they affect the abundance of arthropods and folivory rates. We compared three areas of different successional stages and management, and seasonality in a protected area of Atlantic Forest in southeastern Brazil. The areas selected were anthropic area (“sede”), early and advanced stages of succession. We carried out samplings of birds through 12 fixed points for 13 months and classified species in guilds, grouping the consumers of arthropods between strict and facultative insectivorous. We also proceed a twice bird exclusion experiment (rainy and dry season), comparing arthropod abundance and foliar damage in covered vs. non-covered branches. A total of 186 species of birds have been recorded, with 142 consumers of arthropods. The composition of birds was affected by spatial variation, as the temporal variation presented a diffuse influence. The advanced stage area hosts a higher species richness of specialists, threatened, endemic and with a high degree of environmental sensitivity. The “sede” adds generalist and low degree of sensitivity species. The exclusion of birds resulted in a significant increase in abundance (z=24,682, p = 0) and diversity (z=12,825, p = 0) of arthropods, but this was not reflected in differences in folivory; thus which may be driven by other factors such as the bottom-up effect. The abundance of arthropods showed an inverse relationship with the abundance of strict and facultative insectivorous birds and this control through predation occurred in all areas, suggesting the importance of omnivorous species. The spatial variation of insectivorous birds highlights the potential of each sampled area for maintenance of the functional role of these birds, and this might be considered for management practices.